Peran The Nature Conservacy (TNC) Dalam Pelaksanaan Program Karbon Hutan Berau (PKHB) Di Kabupaten Berau - dwiyuni (Jurnal Sosial-Politika, 2020)
The research showed that in the Berau Forest Carbon Program (BFCP) implementationwas not separated from the vision and mission of The Nature Conservancy (TNC) whichconsistenly protect the forest and increase the livelihood of the forest communitythrough sustainable management of natural resource. This is also not separated fromthe roles of TNC to slow down the climate change by providing a model for sustainable,low-emission development in collaboration with the Government of Berau District. TNCalso plays a role as a facilitator that supports the process of discussion, deep concepts about the conditions, problems and mapping, facilitates the interaction and negotiation, and helps obtain and confirm legal supports from the Ministry of Forestry for a pilot program at district level and supports the improvement of the government and private institution capacity in the relationship between community and low-carbon environment.